2023
DOI: 10.3390/smartcities6050115
|View full text |Cite
|
Sign up to set email alerts
|

System Dynamics Model of Decentralized Household Electricity Storage Implementation: Case Study of Latvia

Armands Gravelsins,
Erlanda Atvare,
Edgars Kudurs
et al.

Abstract: Increasing renewable energy share in total energy production is a direction that leads toward the European Union’s aims of carbon neutrality by 2050, as well as increasing energy self-sufficiency and independence. Some of the main challenges to increasing renewable energy share while providing an efficient and secure energy supply are related to the optimization and profitability of de-centralized energy production systems. Integration of energy storage systems in addition to decentralized renewable energy pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The application of renewable energy sources in micro-CHP and Stirling engine systems is increasingly topical; however, there are still practical challenges. Source intermittency is a significant factor when using solar or wind, while biomass is considered a more stable source [61,62]. Ferreira et al [63] developed and solved a numerical model to compare biomass and solar energy as a heat source for the Stirling engine.…”
Section: Qualitative Analysis-tendencies Of Stirling Engine Biomass C...mentioning
confidence: 99%
“…The application of renewable energy sources in micro-CHP and Stirling engine systems is increasingly topical; however, there are still practical challenges. Source intermittency is a significant factor when using solar or wind, while biomass is considered a more stable source [61,62]. Ferreira et al [63] developed and solved a numerical model to compare biomass and solar energy as a heat source for the Stirling engine.…”
Section: Qualitative Analysis-tendencies Of Stirling Engine Biomass C...mentioning
confidence: 99%
“…The literature suggests that building-integrated solar PV modules have great potential for transforming energy systems [12][13][14], and their application is widely studied for DH in the context of Latvia [15]. The authors of [16] concluded that solar PV with battery storage can be installed in 10% of all households in Latvia without any support policies if electricity prices remain the same. There are certain benefits reported for the application of combined heat and power productions [17] and wood fuels [18,19].…”
Section: Introductionmentioning
confidence: 99%